Agro–Input Use in Peri–Urban Okra Productionin the Greater Accra Region - Abla, D.E. (University of Ghana, 2015)
A series of studies were carried out in the Greater Accra region from October, 2012 to May, 2013 to ascertain agro-input usage in okra production and its effects on quality of production and the produce. Studies comprised a survey, two field studies (an on–farm trial and a field experiment) and one laboratory study. For the survey, data were collected through the administration of questionnaires and analyzed using Statistical Package for Social Sciences (SPSS) software (version 18). A randomized complete block design (RCBD) with three treatments as follows: combination of 25g/L permethrin + 475g/L pirimiphos–methyl insecticide + Propaquizafop–100g Herbicide; 25g/L permethrin + 475g/L pirimiphos–methyl + Imidacloprid insecticides + Propaquizafop–100g herbicide and the Control (no pesticide) for the on-farm experiment and 25g/L permethrin + 475g/L pirimiphos–methyl; Neem extract oil at a rate of 3.3mL/L in a knapsack sprayer and a Control (no pesticide) for the field experiment; was used for the field studies with four replicates, while a completely randomized design (CRD) with three replicates was used for the laboratory study. Data were collected on vegetative, reproductive and quality characteristics of okra. Data from field and laboratory studies were analyzed using Analysis of Variance (ANOVA), Genstat Statistical Package (11th edition). The results showed that the farmers in peri-urban okra production were predominantly male (70%) and used agrochemicals widely in their production. None had used certified okra seed for production. Most of these farmers had only basic education which significantly impacted negatively on their ability to read labels on agrochemicals. On–farm trial produced okra which performed significantly better in terms of plant height, stem girth, leaf production, fresh and dry weights of plants compared to that of the field experiment. The laboratory study showed a 10% rapid deterioration and reduced sliminess of okra from plots treated with a mixture of inorganic agrochemicals and botanicals although these fruits were aesthetically more appealing at harvest compared to the controls.
Thesis (MPhil) - University of Ghana, 2015